Lafaz Musytarak in Surah Al-Baqarah Verse 228 and Its Effect on Fiqh - Aspahani Aspahani; Fahrurrazi Fahrurrazi (Kawanua International Journal of Multicultural Studies, 2021)
Arabic is the richest language in the world with lots of vocabulary, so it cannot be denied that Arabic has a vocabulary with a variety of meanings which is commonly referred to as Lafzul Musytarak. Lafzul musytarak is a word or phrase that has two or more meanings. It is the same with the Qur'an which Allah sent down in Arabic containing various kinds of fiqh laws, but because of the lafaz musytarak in the Qur'an, there are differences of opinion among the scholars in establishing the law. Thus, produced legal products are also different. For example, the word Quru 'is contained in Surah Al-Baqarah verse 228. The pronunciation of Quru’ has a double meaning, It can be for the menstrual period or the holy period. Therefore, the opinion about the iddah period for women who are divorced and still have a menstrual cycle is also different. The results of this study indicate the iddah period for divorced women is different based on the inclination of the scholars in interpreting the word Quru'. Regarding this issue, Fuqaha 'ulama are divided into two opinions. Imam Malik and Shafi'i argue that the meaning of Quru' in Surah Al-Baqarah is a holy period, so the iddah period for divorced women is three times of the holy period. On the other hand, Imam Hanafi and Ahmad Bin Hanbal interpret Quru' as the period of menstruation. Therefore, the iddah period for divorced and menstrual women who are not menopausal is three menstrual periods.